2001
DOI: 10.1002/mrd.1135
|View full text |Cite
|
Sign up to set email alerts
|

Cyclooxygenase‐2 is expressed by cumulus cells during oocyte maturation in cattle

Abstract: Prostaglandins could be involved in various aspects of final differentiation of ovarian follicles. Prostaglandins are generated by the cyclooxygenase (cox) pathway. Until now, the expression pattern of isoforms cox-1 and cox-2 of cyclooxygenase in bovine cumulus-oocyte complexes (COCs) was unknown. Using immunodetection procedure, we demonstrated in the present study that cox-2 was expressed by cumulus cells during in vivo and in vitro maturation. Time course induction of cox-2 expression was investigated duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
54
0
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(60 citation statements)
references
References 60 publications
5
54
0
1
Order By: Relevance
“…24 h (Nuttinck et al, 2002). Notwithstanding the differences in the pattern of PTGS2 expression during the later stages of culture (after 6 h), the increase in PTGS2 expression at 6 h, which occurs just before the time for GVBD (Sirard et al, 1989), supports the idea that prostaglandin production may be important in regulating oocyte maturation and cumulus cell expansion.…”
Section: Discussionmentioning
confidence: 72%
See 3 more Smart Citations
“…24 h (Nuttinck et al, 2002). Notwithstanding the differences in the pattern of PTGS2 expression during the later stages of culture (after 6 h), the increase in PTGS2 expression at 6 h, which occurs just before the time for GVBD (Sirard et al, 1989), supports the idea that prostaglandin production may be important in regulating oocyte maturation and cumulus cell expansion.…”
Section: Discussionmentioning
confidence: 72%
“…Basal expression of PTGS2 increased significantly between 0-6 h, declined between 6-12 h and was unchanged from 12-24 h. The presence of PTGS2 mRNA and protein has previously been measured in cultured bovine COC during maturation, although their expression pattern was somewhat different to what is reported here. It was reported that PTGS2 increased at 6 h to reach maximum concentrations at 12 h after incubation in maturation media containing Gn (Calder et al, 2001;Nuttinck et al, 2002), then decreased at 18 and 24 h (Calder et al, 2001) or continued to increase until …”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Recently, our group demonstrated that AngII stimulates the expression of PTGS2 mRNA in cultured bovine granulosa cells, which was potentiated by LH (Portela et al 2008). The involvement of the PTGS2 pathway in oocyte nuclear maturation has been previously demonstrated in sheep (Murdoch 1988(Murdoch , 1996, cattle (Nuttinck et al 2002, Calder et al 2005, mice (Takahashi et al 2006), humans (Ben-Ami et al 2006), and horses (Dell'Aquila et al 2004). In sheep, the systemic administration of indomethacin (nonselective PTGS inhibitor) resulted in suppression of the cumulus cell expansion and oocyte nuclear maturation, which were reversed by PGE 2 intrafollicular injection (Murdoch 1988(Murdoch , 1996.…”
Section: Introductionmentioning
confidence: 85%